1995
DOI: 10.1038/jcbfm.1995.63
|View full text |Cite
|
Sign up to set email alerts
|

D2 Receptor Blockade by Flunarizine and Cinnarizine Explains Extrapyramidal Side Effects. A SPECT Study

Abstract: Twenty-six patients under treatment with the calcium channel blockers flunarizine (Fz) or cinnarizine (Cz) were examined-with single-photon emission computed tomography using [123I]iodobenzamide as a ligand. The striatal dopamine D2 receptor-binding potential was determined and found to be reduced by 14 to 63% (39.5 +/- 15.0%; p < 0.0001) in patients compared with age-matched control values. This reduction was larger in 12 patients with extrapyramidal symptoms and was only slowly reversible after discontinuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
53
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 17 publications
2
53
1
Order By: Relevance
“…This is similar to the results by Brucke et al with an average onset of the symptoms after 16 months. This time latency is shorter than the results obtained by Gimenez -Roldan, which demonstrated cinnarizine-induced parkinsonism after a mean exposure of 4 (± 4) years 6,19 . The association of both drugs, cz and fz, increased the risk of MD.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…This is similar to the results by Brucke et al with an average onset of the symptoms after 16 months. This time latency is shorter than the results obtained by Gimenez -Roldan, which demonstrated cinnarizine-induced parkinsonism after a mean exposure of 4 (± 4) years 6,19 . The association of both drugs, cz and fz, increased the risk of MD.…”
Section: Discussioncontrasting
confidence: 59%
“…Neuroleptics can induce a variety of MD due to changes in the dopaminergic pathways and it is the second most frequent cause of parkinsonism 7,17,18 . The pathophysiology of these disorders is almost always related to disturbances in the dopamine pathways, mainly by blocking the D2-receptors, like many neuroleptic drugs 1,2,4,5,7,11,19 . Brucke et al demonstrated that studying patients examined with single-photon emission tomography using {123} iodobenzamide as a ligand and it showed the D2 receptor blockade by cz and fz 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the pathophysiology underlying TMZ-induced Parkinsonism remains unclear, a possible mechanism of action, as suggested by previous studies, involves the piperazine component in its chemical structure, similar to flunarizine, thiethylperazine, and perphenazine, that blocks striatal dopamine D2 receptors, thus resulting in an extrapyramidal type of adverse reaction [10,11,24,25]. Some studies have shown that the dopamine D2 receptor activity in the basal ganglia decreases in patients treated with drugs containing the piperazine ring [24,25]. Our results indicated that age could represent an important risk factor in the development of TMZ-associated Parkinsonism, in agreement with other published studies [26].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a substantial part of the PKU patients with an intellectual disability is prescribed DA antagonists that are associated with extrapyramidal symptoms such as parkinsonism. Other agents that negatively influence DA transmission include the calcium channel blockers flunarizine and cinnarizine (Br€ ucke et al 1995) and the antiemetic drug metoclopramide. Although no systematic studies exist, and motor symptoms emerge only after pronounced cerebral DA dysfunction (Cummings et al 2014), prescription of medication that negatively influences DA transmission might carry a risk to cause or aggravate parkinsonian symptoms in PKU patients.…”
Section: Discussionmentioning
confidence: 99%